Refleksi Eksistensi Petani dalam Panggung Sejarah Indonesia - Hasibuan, Yandi Syaputra; Sabrina, Arkini (Jurnal Sejarah Indonesia, 2024)
This article raises issues related to the overall exploitation of farmers in various regions in Indonesia. This paper uses historical methods. The existence of farmers was underestimated because they were merely extras, or more precisely, material for Dutch and Japanese colonial exploitation, both for economic and political interests. This fate then suddenly changed because farmers had joined political party groups and become organizations, such as Pertanu, STTI, BTI, and so on. Unfortunately, the euphoria to support the peasants did not run smoothly because there were clashes with civil society and with those who did not share the same ideology. The result is bloodshed between members of the nation; this is truly ironic. Until then, the New Order was born, and all forms of organizations related to farmers were communized.